Formulation Modeling and Machine Learning In Injectable Drug Product Development: A Review - Dr. Bodkhe Atul Arvind (Asian Journal of Pharmaceutical Research and Development, 2026)
Injectable drug products play a vital role in modern medicine, providing efficient and precise delivery of therapeutics. The development and optimization of injectable formulations require extensive research and development, as well as a deep understanding of the underlying physicochemical properties of the drug and its interactions with excipients. In recent years, machine learning (ML) techniques have emerged as powerful tools for predicting and modeling various aspects of drug formulation, leading to enhanced efficiency and cost-effectiveness in the pharmaceutical industry. This review article provides an overview of the application of ML techniques in the formulation modeling of injectable drug products, highlighting their potential and challenges in improving drug development processes.